IT Governance – An international guide to data security and ISO 27001/ISO 27002, Eighth edition - Calder, Alan; Watkins, Steve (IT Governance Publishing, 2024)
Available for pre-order now! Publishing June 2024! Recommended textbook for the Open University's postgraduate information security course and the recommended text for all IBITGQ ISO 27001 courses In this updated edition, renowned ISO 27001/27002 experts Alan Calder and Steve Watkins: Discuss the ISO 27001/27002:2022 updates; Provide guidance on how to establish a strong IT governance system and an ISMS (information security management system) that complies with ISO 27001 and ISO 27002; Highlight why data protection and information security are vital in our ever-changing online and physical environments; Reflect on changes to international legislation, e.g. the GDPR (General Data Protection Regulation); and Review key topics such as risk assessment, asset management, controls, security, supplier relationships and compliance. Fully updated to align with ISO 27001/27002:2022 IT Governance - An international guide to data security and ISO 27001/ISO 27002, Eighth edition provides: Expert information security management and governance guidance based on international best practice; Guidance on how to protect and enhance your organisation with an ISO 27001:2022-compliant ISMS; and Discussion around the changes to international legislation, including ISO 27001:2022 and ISO 27002:2022. As cyber threats continue to increase in prevalence and ferocity, it is more important than ever to implement a secure ISMS to protect your organisation. Certifying your ISMS to ISO 27001 and ISO 27002 demonstrates to customers and stakeholders that your organisation is handling data securely.